2020
DOI: 10.1155/2020/2636514
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Anthracycline-Based Chemotherapy-Induced Adverse Drug Reactions and Their Impact on Relative Dose Intensity among Women with Breast Cancer in Ethiopia: A Prospective Observational Study

Abstract: Background. e breast cancer chemotherapy leads to diverse aspects of noxious or unintended adverse drug reactions (ADRs) that cause the relative dose intensity (RDI) reduced to below optimal (i.e., if the percentage of actual dose received per unit time divided by planned dose per unit time is less than 85%). Hence, this prospective observational study was conducted to evaluate chemotherapy-induced ADRs and their impact on relative dose intensity among women with breast cancer in Ethiopia.Methods. e study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
6
5
2
Order By: Relevance
“…No significant differences were observed for hematological toxicities, whether they occurred during anthracycline treatment or during taxane administration post anthracycline treatment. Our findings are in line with the previous studies and support the evidence that adding taxane (e.g., paclitaxel) sequentially to the anthracycline-based regimens does not increase the overall incidence and severity of toxicity [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant differences were observed for hematological toxicities, whether they occurred during anthracycline treatment or during taxane administration post anthracycline treatment. Our findings are in line with the previous studies and support the evidence that adding taxane (e.g., paclitaxel) sequentially to the anthracycline-based regimens does not increase the overall incidence and severity of toxicity [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study revealed a positive association between severe chemotherapy-induced toxicities and decreased creatine clearance at baseline among older patients with cancer [ 44 ]. Inconsistent with our findings, lower pretreatment blood counts (e.g., WBC, ANC) and Hgb were previously suggested to be associated with chemotherapy-induced hematological toxicities [ 27 , 36 , 45 ]. Although not confirmed, we speculate that oncologists might have considered patients’ pre-existing hematological conditions in cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Doxorubicin-cyclophosphamide, doxorubicin-cyclophosphamide followed by paclitaxel regimen, cisplatin-paclitaxel regimen, and combination treatment modality of chemotherapy, radiotherapy, and surgery was signi cantly associated with the incidence of neutropenia. The result was consistent with the studies in Denmark, Belgium, and Korea [38][39][40]. This effect was also in line with the recommendation of the National Comprehensive Cancer Network (NCCN) guideline [41].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies report similar levels of vomiting. [ 22 23 ] As compared to nausea, vomiting was identified more frequently in the current study although literature shows that nausea is in fact more frequently occurring,[ 22 23 24 ] further supporting the hypothesis that nausea was under-reported.…”
Section: Discussionsupporting
confidence: 76%